Comparative Pharmacoepidemiological Assessment of Antihypertensive Drugs Administration Structure in Pregnant Women in Routine Medical Practice in Kursk and Chisinau - S. V. Povetkin; V. I. Gikavyj; N. G. Bachinski; O. V. Levashova; A. A. Kornilov; L. A. Podgurski; L. M. Tsurkan (Рациональная фармакотерапия в кардиологии, 2022)
Aim. To study the structure of antihypertensive drugs prescription in pregnant women in routine practice in Kursk and Chisinau.Material and methods. The study design was observational descriptive cross-sectional. Authors conducted a survey of doctors in medical organizations in Kursk and Chisinau in 2017-2018.Results. Respondents from Kursk and Chisinau preferred methyldopa in prescriptions of central alpha-adrenergic receptor agonists. Doctors from Chisinau used clonidine in 14.3% of cases. The leading place in the group of calcium channel blockers belonged to short-acting nifedipine. Among beta-blockers in Kursk, doctors most often prescribed bisoprolol (43.3%), metoprolol (21.7%) and nebivolol (13.3%), while in Chisinau the preference was given to metoprolol (32.1%), atenolol (19.6%) and bisoprolol (16.1%). From the group of diuretics, Kursk doctors mainly prescribed hydrochlorothiazide (10%), indapamide (6.7%); in Chisinau, indapamide was the leader (19.6%), hydrochlorothiazide was used less frequently (7,1%). From the class of alpha-blockers, prazosin occupied the leading position among respondents in Kursk, and terazosin in Chisinau.Conclusion. The priority drug classes in both regions were calcium channel blockers, central alpha-adrenergic receptor agonists and beta-blockers. A small number of not recommended drugs prescriptions have been registered. In general, the prescribed treatment corresponded to the current guidelines and protocols for the management of patients with arterial hypertension during pregnancy.